Leyendo mi cuento cholito en el valle de Supay - Ortiz Asencios, Ana Celi (2019)
The present work of professional sufficiency is once the designing of a learning activity was based on, with the competition He Gets In Touch Orally in his mother tongue and the performance “ Take Part In conversations, dialogs or listening-in tales legends, rhymes, riddles and other stories of the oral tradition. Expect his turn to talk, listening-in while his inter-radio speaker talks, ask and respond on what he is interested in knowing to him or what he has understood with the intention of obtaining information, that it will result in that the children of 5 years of Trujillo's City manifest themselves of spontaneous way notifying what he understood of the read story orally._x000D_ _x000D_ On the other hand, the oral expression will allow the children, a better interaction and integration with the family, the society and the culture; This competition has like purpose that children communicate themselves orally and express their opinion on what more I taste them of the text contents.